2010
DOI: 10.1002/ejic.201000382
|View full text |Cite
|
Sign up to set email alerts
|

Application of DFT Methods in the Study of VIVO2+–Peptide Interactions

Abstract: VIVO2+ complexes formed by histidylglycylglycine (HisGlyGlyH), glycylglycylhistidine (GlyGlyHisH), glycylglycylcysteine (GlyGlyCysH2), N‐glycyl‐bis(imidazol‐2‐yl)methylamine (Gly–BIMA), N‐glycyl‐bis(pyridin‐2‐yl)methylamine (Gly–BPMA), salicylglycyl‐L‐alanine (SalGly‐L‐AlaH2) and 1,2‐bis(2‐hydroxybenzamido)benzene (H2hybeb) in their fully deprotonated form were studied by density functional theory (DFT) methods. They are characterised by different total electric charges, total equatorial charges and number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 95 publications
1
14
0
Order By: Relevance
“…From the overall composition the weakest bond is with H 2 O reflected from bond length data as well as from orbital composition. The results are in good agreement as per the reports appeared elsewhere [70][71][72].…”
Section: Frontier Molecular Orbitals Analysissupporting
confidence: 92%
“…From the overall composition the weakest bond is with H 2 O reflected from bond length data as well as from orbital composition. The results are in good agreement as per the reports appeared elsewhere [70][71][72].…”
Section: Frontier Molecular Orbitals Analysissupporting
confidence: 92%
“…Several approaches were used: for example, Saladino and Larsen used a scalar relativistic, spin‐unrestricted, open‐shell Kohm‐Sham calculation for simulating A N for seven V IV O 2+ species,67 whereas Neese showed that for Cu 2+ complexes hybrid functionals, such as B3LYP or PWP1, give better predictions than functionals based on the generalized gradient approximation like BP or BLYP 66b. In the absence of systematic DFT studies regarding V IV O 2+ species, we recently performed preliminary simulations at different level of theory, and the best results have been obtained with half‐and‐half hybrid functional BHandH, whereas the choice of the basis set, 6‐311+g(d,p) or 6‐311g(d,p), is less important 68. The results are illustrated in Figure 8.…”
Section: Resultsmentioning
confidence: 99%
“…This approach was used to characterize the active site, the catalytic cycle and the structure of other metal proteins [157] and consists in the simulation of the 51 V hyperfine coupling tensor A of a V IV O complex which can be considered a model for the active site. When 51 V A is calculated using the functional BHandHLYP and the basis set 6-311g(d,p), a good model of the V sites should give A z values in agreement with the experimental one with a deviation around 2-3% [158,159,160,161,162,163,164]. Therefore, DFT methods may be used to predict A z for a V IV O 2+ species, and vice versa, to predict an unknown structure from its A z value.…”
Section: Immunoglobulinsmentioning
confidence: 99%